The postmodern pulse of postproverbials in African cultural space (2019)
The last few decades of the twentieth century witnessed influx of Western theories into African scholarship. This is gradually being deconstructed with preponderant discourse of decolonization, as a contemporary theme in postcolonial Africa. The practice of postproverbiality, which resonates during the same historical phase, indicates transgressive subversion of alternate creations that run parallel with postmodern temperance. This study, therefore, examines the postmodern pulse as a significant component of the aesthetics and values of postproverbiality pulse in contemporary African literary cum cultural space. The aim is to foreground the theoretical significance of postmodernism as the compelling forte of postproverbiality and in furtherance, to articulate the postmodern presence in contemporary African literary space. Part of the research objectives is to critically analyse the socio-cultural content and context of postproverbials and explore the postmodern pulse of selected postproverbial forms as the prostheses of conventional African proverbs.